Efficacy of Topical Testosterone in Hypospadias Patients Presenting with Microphallus: Efficacy of Topical Testosterone in Hypospadias Patients - Khan, Shahid; Azam, Amber; Jelani, Umama; Zara, Zaibi; Qureshi, Waleed Anjum; Khan, Muhammad Ahsan (Pakistan Journal of Health Sciences, 2025)
Hypospadias, a common congenital anomaly in males, is often linked with microphallus, complicating surgery. Preoperative androgen therapy may enhance penile size and outcomes, though most studies focus on intramuscular routes. Limited data exist on topical testosterone, especially locally. Objectives: To assess the effectiveness of topical testosterone in increasing penile length in children with hypospadias and microphallus. Methods: This quasi-experimental study was conducted at the Department of Plastic Surgery, Northwest General Hospital, spanned six months from November 2024 till May 2025. A total of 195 boys aged 1–10 years with hypospadias and microphallus received 5% topical testosterone cream, applied four times daily for 45 days. Stretched penile length was measured before and after treatment. A ≥50% increase defined treatment success. Data were analyzed using SPSS version 25.0; significance was set at p≤0.05. Results: Median penile length increased from 42 mm (IQR: 8 mm) to 60 mm (IQR: 21 mm). Mean length rose from 41.32 mm to 59.18 mm (p < 0.001). A ≥50% increase was seen in 52.3% of patients. No significant link was found between efficacy and age (p = 0.316) or hypospadias type (p=0.118). Conclusions: Topical testosterone effectively increases penile length in children with hypospadias and microphallus, regardless of age or subtype.